2021
DOI: 10.1051/0004-6361/202140512
|View full text |Cite
|
Sign up to set email alerts
|

ATOMIUM: The astounding complexity of the near circumstellar environment of the M-type AGB star R Hydrae

Abstract: Evolved low- to intermediate-mass stars are known to shed their gaseous envelope into a large, dusty, molecule-rich circumstellar nebula which typically develops a high degree of structural complexity. Most of the large-scale, spatially correlated structures in the nebula are thought to originate from the interaction of the stellar wind with a companion. As part of the ATOMIUM large programme, we observed the M-type asymptotic giant branch (AGB) star R Hydrae with the Atacama Large Millimeter/submillimeter Arr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…We took the calibrated data for all ALMA configurations combined, excluding channels with line emission, and fit a uniform disc (UD) to the visibilities (as in [65]). This gave a diameter of 16.7 mas, containing 8.0 mJy.…”
Section: Agb Angular Diametermentioning
confidence: 99%
“…We took the calibrated data for all ALMA configurations combined, excluding channels with line emission, and fit a uniform disc (UD) to the visibilities (as in [65]). This gave a diameter of 16.7 mas, containing 8.0 mJy.…”
Section: Agb Angular Diametermentioning
confidence: 99%
“…At a projected distance of 100 au from the centre of the star, the SiO/CO ratio is over two orders of magnitude smaller in Mira A than in R Dor and EP Aqr. The SiO emission of the CSEs of other low mass-loss-rate oxygenrich AGB stars, such as W Hya (Takigawa et al 2017;Hoai et al 2021), RS Cnc (Winters et al 2021), R Leo (Fonfría et al 2019a,b), R Hya (Homan et al 2021) has also been observed at ALMA; in general, the SiO emission, while being significantly more compact than the CO emission, extends beyond 150 au, providing additional evidence for the specificity of Mira Ceti.…”
Section: Confinement At Short Distances Of the Sio Emissions Outside ...mentioning
confidence: 99%
“…The shaping mechanism(s) of the wind of AGB and post-AGB stars still represent(s) a missing piece in our understanding of their mass loss, and ultimately the formation of the structures seen in planetary nebulae (Decin et al 2020). By combining spatially resolved observations of the circumstellar environment through several molecular transitions, constraints are placed on the masses of the new companions for both π 1 Gru (≲ 1.1 M ⊙ ; Homan et al 2020) and R Hya (≳ 0.65 M ⊙ ; Homan et al 2021). For the S-type star W Aql, observations of halide molecules show that its AlF abundance exceeds the solar fluorine abundance, confirming that fluorine synthesized in situ is already brought to the surface of the AGB star and expelled in its circumstellar environment (Danilovich et al 2021).…”
Section: Introductionmentioning
confidence: 99%